How fuel poverty affects subjective well-being: Panel evidence from Germany - Philipp Biermann (University of Oldenburg, Department of Economics, 2016)
This paper uses panel data on life satisfaction of about 40,000 individuals in Germany from 1994 to 2013 to analyze the relationship of subjective well-being and several measures of fuel poverty. We study fuel poverty and its effects on life satisfaction in terms of incidence, intensity and in comparison to income poverty. We find a negative and significant effect of fuel poverty and subjective well-being. The effects are comparable in magnitude to those of other important factors of life satisfaction. The impact we find is beyond the effect of mere income poverty. We classify measures of fuel poverty into several types and find that there is a difference with respect to the well-being effects depending on the type of measure. Our findings confirm the argument of the recent literature that fuel poverty is an important issue and should be on the agenda of policy makers.
Keywords: I3; D12; C2; Q4; 330; fuel poverty; consumer welfare; subjective well-being; Germany